2004
DOI: 10.1682/jrrd.2003.10.0158
|View full text |Cite
|
Sign up to set email alerts
|

Computer-automated tinnitus assessment using patient control

Abstract: Abstract-A need exists for a standardized tinnitus evaluation tool to measure "acoustic" parameters of tinnitus. An automated tinnitus evaluation system has been developed in this laboratory, consisting of a patient-controlled touch-screen computer monitor, main computer, and Programmable Auditory Laboratory 3000 (PAL 3000) (a custom-built signal conditioning module). The system obtains and records data from tinnitus patients, including hearing thresholds and the pitch and loudness of their tinnitus. New featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…Some studies have shown good loudness test-retest reliability over a period ranging from several days [4,6,15,31,38,39] to several months [12,34], with less than 5 dB difference between sessions, whereas other studies have reported greater variability [16,21,40], putting into question the validity of this measure for tinnitus diagnosis and follow-up. Herein we investigate the proposition that the assessment of frequency likeness ratings over the entire frequency span will increase the reliability of loudness judgments by providing participants with several opportunities to judge tinnitus loudness.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown good loudness test-retest reliability over a period ranging from several days [4,6,15,31,38,39] to several months [12,34], with less than 5 dB difference between sessions, whereas other studies have reported greater variability [16,21,40], putting into question the validity of this measure for tinnitus diagnosis and follow-up. Herein we investigate the proposition that the assessment of frequency likeness ratings over the entire frequency span will increase the reliability of loudness judgments by providing participants with several opportunities to judge tinnitus loudness.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a typical approach would consist in adjusting a sound until the tinnitus subject has the impression that the frequency resembles his/her perceived pitch. Automated procedures using a computer have also been published, in which the subject, e.g., makes higher/lower judgments or gives judgments which of two sounds is closer to the tinnitus pitch (Henry et al, 2004). Tinnitus pitch matching has revealed that tinnitus pitch is usually in the high-frequency region.…”
Section: Introductionmentioning
confidence: 99%
“…8 Other studies have also introduced automated tests for tinnitus quantification. Henry et al [5][6][7][8] have been developing and using an automated process for tinnitus psychoacoustic assessment that consists of hardware and software for evaluation of tinnitus loudness match, pitch match, minimum masking level, and residual inhibition. In comparison, the web-based system we introduced is currently designed to quantify only tinnitus frequency, but is easily available over the web and could be performed with minimal equipment.…”
Section: Resultsmentioning
confidence: 99%